AKTIVITAS PENGELOLAAN LAYANAN PUBLIK BERBASIS WEBSITE DI DINAS KOMUNIKASI DAN INFORMATIKA BANYUMAS (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2021)
This research is motivated by the many problems of government activities that are currently increasingly being highlighted by the community, especially those related to public services organized by the Government agencies of the Communication and Informatics Office of Banyumas Regency. One problem is that public institutions, which in fact act as information providers, are led to work continuously by preparing a database of information for publication. Thus the purpose of this study is to determine the activities of public service information management in realizing the quality of communication in the Communication and Informatics Office of Banyumas Regency. The purpose of this research is to find out how public servants are a way for the Communication and Information Technology Office to provide transparent, accurate, fair services to the public, so that public agencies can produce quality services. Furthermore, documenting information, which is an activity of recording and storing all information that has been obtained in the work unit by authenticating information, coding the information and its relation to the packaging of information.